Redox Imbalance and Antioxidant Defenses Dysfunction: Key Contributors to Early Aging in Childhood Cancer Survivors - Vanessa Cossu; Nadia Bertola; Chiara Fresia; Federica Sabatini; Silvia Ravera (MDPI AG, 2024)
Survival rates for childhood cancer survivors (CCS) have improved, although they display a risk for early frailty due to the long-term effects of chemo/radiotherapy, including early aging. This study investigates antioxidant defenses and oxidative damage in mononuclear cells (MNCs) from CCS, comparing them with those from age-matched and elderly healthy individuals. Results show impaired antioxidant responses and increased oxidative stress in CCS MNCs, which exhibited uncoupled oxidative phosphorylation, leading to higher production of reactive oxygen species, similar to metabolic issues seen in elderly individuals. Key antioxidant enzymes, namely glucose-6-phosphate dehydrogenase, hexose-6-phosphate dehydrogenase, glutathione reductase, glutathione peroxidase, catalase, and superoxide dismutase, showed reduced activity, likely due to lower expression of nuclear factor erythroid 2-related factor 2 (Nrf2). This imbalance caused significant damage to lipids, proteins, and DNA, potentially contributing to cellular dysfunction and a higher risk of cancer recurrence. These oxidative and metabolic dysfunctions persist over time, regardless of cancer type or treatment. However, treatment with N-acetylcysteine improved Nrf2 expression, boosted antioxidant defenses, reduced oxidative damage, and restored oxidative phosphorylation efficiency, suggesting that targeting the redox imbalance could enhance long-term CCS health.